Association between Personal Hygiene and Incidence of Soil-Transmitted Helminthiasis among Workers at Widodaren Plantation in Jember Regency - Zulaikha Rizqina Rahmawati; Bagus Hermansyah; Erfan Efendi; Yunita Armiyanti; Yudha Nurdian; Wiwien Sugih Utami (Faculty of Medicine, University of Jember, 2020)
Soil-Transmitted Helmithiasis is an infection caused by intestinal nematode worms which in the process of transmission requires soil as media to fullfil its life cycle from non-infective forms to infective forms. The number of infections is influenced by personal hygiene. Personal hygiene consists of the habit of washing hands, cutting nails, eating, defecating and ownership of latrines, and the use of personal protective equipment. This study used a cross sectional research design conducted at Widodaren Plantation with 68 people of samples. Stool examination was determined by kato-katz method, sedimentation, and floatation to detect the presence of Soil-Transmitted Helminth (STH) eggs, while personal hygiene was assessed using questionnaires. Questionnaire and stool examination datas were processed using SPSS data analysis with chi-square method. The results of this study found 26 respondents who were positive for soil-trasmitted helminthiasis infection. The most frequent worm species obtained in this study were Ascaris lumbricoides (57.7%), followed by multiple infections between Hookworm and A. lumbricoides (21.3%), and Hookworm (19.2%). In the chi-square analysis the results were significant between personal hygiene and soil-transmitted helminthiasis with p value of 0,000 (p <0.05). So, it can be concluded that a bad personal hygiene factor has a significant relationship to the incidence of Soil-Transmitted Helminthiasis at Widodaren Plantation. Keywords: Personal hygiene, STH, plantation